Activated electric arc furnace slag as an effective and reusable Fenton-like catalyst for the photodegradation of methylene blue and acid blue 29. (1st July 2017) - Nasuha, N.; Ismail, S.; Hameed, B.H.
Abstract: In this work, an activated electric arc furnace slag (A-EAFS) was investigated as an effective Fenton catalyst for the photodegradation of methylene blue (MB) and acid blue 29 (AB29). Fourier transform infrared spectroscopy and UV–visible absorption analyses indicated that A-EAFS offers additional Fe3 O4 because of the changes in the iron oxide phase and the favorable response to visible light. It has been found that the highest degradation efficiency can reach up to 94% for MB under optimal conditions of 1 g L −1 of A-EAFS, 20 mM H2 O2, and pH 3. The optimal conditions for AB29 were 0.1 g L −1 A-EAFS, 4 mM H2 O2, and pH 3 to reach 98% degradation efficiency. Visible light enhanced the degradation of both dyes. In addition, A-EAFS, could be easily separated magnetically, exhibited good chemical stability after seven successive photodegradation cycles. Highlights: Activated electric arc furnace slag reveals excellent visible-light photocatalyst. A-EAFS is active at the visible region higher than 400 nm. A-EAFS is highly efficient up to seven cycles of magnetic separation and recovery.